Distribution and Bionomic of Sand Flies in Five Ecologically Different Cutaneous Leishmaniasis Foci in Morocco. (17th September 2013) - Faraj, Chafika; Adlaoui, El Bachir; Ouahabi, Souad; El Kohli, Mohamed; El Rhazi, Mohamed; Lakraa, Lhoussine; Ameur, Btissam
Abstract : Cutaneous and visceral leishmaniases are endemic in Morocco. Their geographical distribution is well known. It has been related to bioclimatic factors. However, in 2008, two new cutaneous leishmaniasis foci appeared out of the known risk areas. Hence, we have undertaken this entomological survey in five foci situated in different bioclimatic areas to better understand the distribution and the epidemiology of this disease. Results of this study, undertaken during 2011, showed the predominance of Phlebotomus sergenti (55.8%) followed by Ph. perniciosus (12.9%), Ph. longicuspis (12.3%), and Ph. papatasi (12.0%). Ph. sergenti was active during 6 months in subhumid area and 8 months in arid, semiarid, and Saharan areas. Compared to previous studies, our results show a rise in Ph. sergenti abundance and an extension of its activity period. These results could explain the increase in anthroponotic cutaneous leishmaniasis incidence in Morocco and its extension to new nonendemic regions. Ph. perniciosus and Ph. longicuspis have also displayed a large distribution and a long activity period indicating a high potential risk of Leishmania infantum transmission in the studied areas.